2013
DOI: 10.1021/jm400401y
|View full text |Cite
|
Sign up to set email alerts
|

Guaifenesin Derivatives Promote Neurite Outgrowth and Protect Diabetic Mice from Neuropathy

Abstract: In diabetic patients, an early index of peripheral neuropathy is the slowing of conduction velocity in large myelinated neurons and a lack of understanding of the basic pathogenic mechanisms hindered therapeutics development. Racemic (R/S)-guaifenesin (1) was identified as a potent enhancer of neurite outgrowth using an in vitro screen. Its R-enantiomer (R)-1 carried the most biological activity, whereas the S-enantiomer (S)-1 was inactive. Focused structural variations to (R/S)-1 was conducted to identify pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The broad-spectrum nicotinic antagonists hexaarticle; doi:10.1172/JCI88321DS1; and previously described in ref. 28) identified pirenzepine, a selective M 1 R antagonist (29), as able to induce a dose-dependent (3 to 100 nM) increase of total neurite outgrowth from neurons derived from normal rats ( Figure 1, A and B). This effect was mimicked by 30 nM VU0255035, a structurally dissimilar but also selective M 1 R antagonist (30) (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…The broad-spectrum nicotinic antagonists hexaarticle; doi:10.1172/JCI88321DS1; and previously described in ref. 28) identified pirenzepine, a selective M 1 R antagonist (29), as able to induce a dose-dependent (3 to 100 nM) increase of total neurite outgrowth from neurons derived from normal rats ( Figure 1, A and B). This effect was mimicked by 30 nM VU0255035, a structurally dissimilar but also selective M 1 R antagonist (30) (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…These ingredients were linked to diverse antidiabetic activities in previous studies and were computationally confirmed here. For example, 1-OCTEN-3-OL from Ge-Gen and 2-Acetyl-1-methylpyrrole from Gan-Cao were found to be antioxidants involved in the improvement of diabetes [50, 63, 64]; guaifenesin from Huang-Qin promoted neurite outgrowth and protected diabetic mice from neuropathy [61]. In particular, several core ingredients from Huang-Lian, berberine bisulfate, columbamine, coptisine, epiberberine, jatrorrhizine, oxyberberine, dehydrocheilanthifoline, and berberine were reported to have hypoglycemic and antidiabetic actions through the regulation of glucose metabolic effects and reduction of oxidative stress injury [51–59].…”
Section: Resultsmentioning
confidence: 99%
“…Back in 2003, during a study of a series of TAGEs, we found that the registered drug guaifenesin 38 has the property of spontaneous resolution . Guaifenesin is usually classified as the centrally acting muscle relaxant with expectorant properties e, but there is evidence that it has other types of activity . In this last paper, the various activities of individual enantiomers have also been demonstrated.…”
Section: Using Direct Methods To Obtain Single Enantiomer Apismentioning
confidence: 99%